Correlation between Blood Group Phenotypes and Incidence of Helicobacter pyloriInfection - Shaymaa Hasan Abbas; Sura Abbas Khdair; Noor Wafaa Hashim; Lubab Tarek Nafea; Yasmeen Jamal Ali; Farah Nazar Mahmood (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Helicobacter pylori is a gram-negative, spiral and flagellated bacteria.Thisinfection might be present in more than 50 percent of people in the world.It has been found for several years that gastric carcinoma occur more frequently in patients with blood group A, while duodenal ulcer had been associated with blood group O. Methodology: This is a prospective randomized controlled study in which patients who were newly diagnosed with H. pylori infectionsincluded. Sixty-one, selected Iraqi patients were (37 female and 24 male), with age ranges between (17-70) years. The Patients who enrolled in this study were divided according to (ABOBlood groups) into four groups.Data were collected from the patientsthrough direct interview included the age, gender, history of the disease, blood group, and Rhesus (Rh) factor. Results: In this study thelargest proportion(42.62%) of H. pylori infected patients according to ABO phenotypes was found in blood group O, and the smallest proportion(8.2%) was in blood group AB. Though the mean age of H. pylori infected patients in blood group O was higher than the other blood groups and less mean age was in blood group B.The female patients exhibited greater percentages of H. pylori infection than males for blood groups A, blood groups B, and blood group AB except for O blood groups patients where proportion of male was more than female. On the other hand the percentage of H. pylori infected patients in this study according to Rh factor distributed as follow: in +Rh factor (78.69%) and -Rh factor (21.31%).Conclusion:The incidence of H. pylori infection is high in patients with blood group O so, the blood group phenotypes may play a role in H. pylori infection. Meanwhile there was no correlation between age, and Rh status with distribution of H. pylori infection among different ABO phenotypes patients.However, larger sample size is needed to further clarify this association.